Research on the thermal characteristics of bending hybrid piezoelectric actuators under different exciting methods. (August 2017) - Liu, Yingxiang; Shi, Shengjun; Wang, Dingwen; Chen, Weishan; Xu, Dongmei
Abstract: Bending hybrid piezoelectric actuators have merits of large flexibility on dimensions as the only restriction is the symmetry in structure. Furthermore, they can be used for linear or rotary driving either, depends on the type of the rotor. This work focuses on the exciting methods for the bending hybrid vibrations, which are evaluated by the comparison between their thermal characteristics. Totally, five exciting methods are proposed and tested, they are: half pieces of PZT plates with converse polarizations, whole pieces of PZT plates with two partitions of converse polarizations, whole pieces of PZT plates with two partitions of the same polarization, whole pieces of PZT plates with four partitions of converse polarizations and whole pieces of PZT plates with four partitions of the same polarization. Five prototypes with the same dimensions are fabricated under the proposed five exciting methods, respectively. Their surface temperature changes are measured under no-load condition in time domain. The effects of the temperature on the electromechanical coupling factors are measured. This work can guide the design of piezoelectric actuators operated in bending hybrid modes.